"Down with the Monarchy": Iran's Republican Moment of August 1953. Issue 2 (4th March 2017) - Randjbar-Daemi, Siavush
Abstract : The purpose of this article is to explore and analyze Iran's "Republican Moment" of 16‒19 August 1953, arguably the last concerted effort to abolish the monarchy and establish a republican order in the county prior to the Revolution of 1978‒79. By drawing on a broad range of primary source materials that have thus far remained relatively understudied by existing scholarship, such as the political press of those crucial days, the essay will attempt to shed light on a number of significant domestic developments which impacted the outcome of the actual coup of 19 August 1953. A further attempt will be made to explain the importance of calls in favor of the Republic and the premier Mohammad Mosaddeq's refusal to take heed of them. The paper will also explore the diverse origins of the Republican platform and its impact on both the urban crowd and the political elite.